DUTIES AND FUNCTIONS KELOMPOK SADAR WISATA IN THE ISLAND PENYENGAT TANJUNG PINANG PROVINCE KEPULUAN RIAU - M. Fhachri; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This reseach aims to know about duties and functions of pokdarwis in penyengat island, tanjung pinang city. This reseach was used qualitative method with descriptive approach to discrib the condition and explain that happened by collecting the data and information on thevield. And the informant key in this reseach was one chief of pokdarwis and sixteen member of pokdarwis in penyengat island, tanjung pinang city. In this research, the thechnique to collecting the data used interview, obsevation and documentation. Based on  the result of the research, can be concluded that all pokdarwis divisions of penyengat island have done all the thing that refer to the grand theory that used. But their was also the thing that haven’t done by the  member of pokdarwis.         Keyword: Kelompok Sadar Wisata, dutys, functions and Penyengat island